The effect of reflective thinking on the teaching practices of preservice physical education teachers - (:unkn) unknown (WESTERN AUSTRALIAN INST EDUCATIONAL RESEARCH INC, 2015)
The purpose of this study is to determine the effect of reflective thinking on the professional teaching practices of preservice physical education teachers and to explore their reflective levels. Within the qualitative research paradigm, action research was used to gain a deeper understanding of the reflective experiences of preservice physical education teachers. Data was derived from reflective journals, interviews, and video recordings of micro teaching sessions. The content analysis method was used to analyse the data. Results indicated that at the beginning of their reflection, the participants were at the technical level of the reflective framework; then they started to reflect at both contextual and dialectical levels. Additionally, the reflective thinking framework allowed preservice physical education teachers to focus on their application of their knowledge and enabled them to generate a conscious awareness of their professional development. As a result, preservice physical education teachers displayed professional development in proper planning, time management, and use of school facilities. Furthermore, students' developmental levels and teaching approaches through their experiences and their reflections on these experiences were determined.